Dampak Perubahan Penggunaan Lahan Terhadap Limpasan Permukaan dan Laju Aliran Puncak Sub DAS Gajahwong Hulu Kabupaten Sleman - Rahardian, Andiri; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Upstream Gajahwong Sub-Watershed included in Yogyakarta Urban Agglomeration Region and regional development of tourism that utilizes the beauty of the slopes of Mount Merapi also the support accessibility (Solo-Magelang-Semarang road; this condition is assumed to be the cause of landuse changes, followed by vegetation land shrinkage. The shrinkage’s result is water catchment areas reduction that disrupts the Sub-Watershed hydrology function. One of indication is the increasing flood discharge that can be seen from the changes in surface runoff and peak flow rate. This research aims to assess the impact of landuse change on surface runoff and peak flow rate in Gajahwong Sub-Watershed using a quantitative method that consists of spatial and mathematic analysis with SCS and Rational Method. The results showed that the landuse changes impact on increasing surface runoff and peak flow rate. The surface runoff in year 2002 amounted to 3.073 mm with a peak flow rate of 98.02 m³/sec then increased to 3.901 mm with a peak flow rate of 101.65 m³/sec in year 2011. The landuse changes that occur tend to built landuse which was followed by vegetation shrinkage and impact on the increase in surface runoff and peak flow rate. Predictions in year 2031 also showed an increase in surface runoff and peak flow rate, if there is a tendency of landuse changes linearly as landuse changes in year 2002 – 2011. Alternative analytical efforts to handle surface runoff and peak flow rate showed that by combining the development of Green Open Space with water conservation technology (Biopori and Infiltration Wells) can reduce surface runoff and peak flow rate.